2022
DOI: 10.3390/healthcare10102010
|View full text |Cite
|
Sign up to set email alerts
|

Basic Differences and Most Common Findings in Ultrasound Examinations of Musculoskeletal System in Children: A Narrative Literature Review

Abstract: We present basic differences in the musculoskeletal ultrasound examinations between adults and children. Examiners who deal with adults on a daily basis have shared concerns about examining children. Such concerns may arise from the different approach to child ultrasounds, but they also come from differences in anatomical characteristics according to developmental age. We discuss the presence of growth plates, as well as non-mineralized parts of the bones. We also refer to the pathologies most often found in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Nasal bones in younger children are less prominent and not fully ossified. The ongoing process of ossification results in anatomical variations during different stages of childhood, potentially contributing to the increased difficulty of utilizing ultrasonography for fracture detection [ 23 ]. Additionally, a study involving 423 patients with nasal bone fractures revealed significant differences in the most prevalent fracture types between children under 12 years old and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal bones in younger children are less prominent and not fully ossified. The ongoing process of ossification results in anatomical variations during different stages of childhood, potentially contributing to the increased difficulty of utilizing ultrasonography for fracture detection [ 23 ]. Additionally, a study involving 423 patients with nasal bone fractures revealed significant differences in the most prevalent fracture types between children under 12 years old and adults.…”
Section: Discussionmentioning
confidence: 99%
“…US examination of the musculoskeletal system differs (anatomically and histologically) between children [ 27 ], adults and elderly people. For instance, while the main goal of US examination in newborns is perhaps to assess the hip joint for congenital hip dysplasia, in elderly people it is to evaluate the body composition for diagnosing sarcopenia [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unstable or displaced lesions require surgical intervention, usually through arthroscopic methods. Generally, stable lesions have better outcomes compared to unstable ones [95][96][97].…”
Section: Clinical Applicationsmentioning
confidence: 99%